2015
DOI: 10.1007/s00405-015-3710-x
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic and predictive value of excision repair cross-complementation group 1 (ERCC1) protein in 1288 patients with head and neck squamous cell carcinoma treated with platinum-based therapy: a meta-analysis

Abstract: ERCC1 has a potential to become predictive and prognostic factor enabling treatment tailoring in HNSCC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 49 publications
2
22
0
Order By: Relevance
“…In a meta-analysis of 1,288 HNSCC patients receiving platinum-based therapy, Bišof et al reported that ERCC1 may be a predictive and prognostic factor for individualized therapies for HNSCC patients (45). Our findings also suggest that ERCC1 may be a predictive biomarker for response to chemotherapy with 5-FU/cisplatin in HNSCC patients.…”
Section: Discussionsupporting
confidence: 70%
“…In a meta-analysis of 1,288 HNSCC patients receiving platinum-based therapy, Bišof et al reported that ERCC1 may be a predictive and prognostic factor for individualized therapies for HNSCC patients (45). Our findings also suggest that ERCC1 may be a predictive biomarker for response to chemotherapy with 5-FU/cisplatin in HNSCC patients.…”
Section: Discussionsupporting
confidence: 70%
“…7 Furthermore, results of biomarker analyses can be notoriously inconsistent, making it difficult to draw robust conclusions. 8 Some studies might show negative or discrepant results, while the same biomarker might clearly demonstrate positive associations in other studies-for example, CCND1, 9 cMET, 10 p16, [10][11][12] EGFR, 13 and ERCC1. 14 challenges.…”
Section: Opportunities and Challenges In Biomarker Developmentmentioning
confidence: 99%
“…Furthermore, results of biomarker analyses can be notoriously inconsistent, making it difficult to draw robust conclusions . Some studies might show negative or discrepant results, while the same biomarker might clearly demonstrate positive associations in other studies—for example, CCND1, cMET, p16, EGFR, and ERCC1 . Plausible reasons for such discrepancies might include (a) small sample sizes with inadequate controls; (b) differing study populations with true clinical variability; (c) differing treatment modalities; (d) variations in the biomarker assay, for example, different technological platforms used for detection and measurement; (e) differences in the biomarker source, for example, tissue vs liquid biopsy, or fresh vs fixed tissue; (f) varied antibody specificities and binding affinities among different batches or vendors; (g) biomarker instability, with a risk of false positivity or false negativity; (h) differing statistical testing methods; and (i) other methodological differences between studies, for example, evaluation of mRNA vs protein expression …”
Section: Opportunities and Challenges In Biomarker Developmentmentioning
confidence: 99%
See 2 more Smart Citations